ANALISIS KEUNGGULAN BERSAING KOPI KENANGAN DI JAKARTA SELATAN - Muhammad Hazbi Gifari (2021)
This research is aimed at analyzing the influence of business location, service quality and innovation on the competitive advantage of memorable coffee in South Jakarta. The population chosen in this study were the coffee consumers who had been to the memory coffee shop located in South Jakarta. The sample collection technique chosen was non-probability sampling with its type, namely purposive sampling. Sources of data in this study were obtained from distributing questionnaires to 100 respondents. The analytical tool used to assist this research is SmartPLS 3.0. Furthermore, the results given in this study are (1) business location has a significant effect on competitive advantage. (2) service quality has no significant effect on competitive advantage. (3) innovation has a significant effect on competitive advantage.